CULTURAL INTELLECT POST PANDEMIC – Preparedness for Online and Offline Work Environment. (International Journal of Food and Nutritional Sciences, 2022)
Civilizations across the globe have contributed to the present status of communication both at personal and corporate level. Intercultural communication helps us understand the diverse work place norms and strengthen the art of communicating verbally and non- verbally. The very human nature of adaptation leads to the identification of similarities and work differences across cultures. The world mastered this art by being agile, open minded and becoming culturally self-aware. Pre pandemic cross culture communication rested on understanding and exchange of human behavior across cultures in terms of values, beliefs, corporate norms, skills, knowledge and experience prevailing in a nation. With the pandemic, the learning and sharing the insights gets extended not only in terms of technology in industry, merchandise, analytics, engineering and team collaborations but also in terms of understanding the new normal societal standards. It calls for not only revisiting the work standards in terms of hygiene, social distancing, government and regulatory guidelines but also learn to work with virtual teams. So it is establishing the learning insights where there is no past experience of face to face interaction, non-verbal gestures and interpretation of voice modulation. The new normal forces to redefine cultural acumen for leadership, personality, conflict and negotiations, corporate culture and virtual group dynamics globally with new insights.